Hepatic Insulin Resistance Model in the Male Wistar Rat Using Exogenous Insulin Glargine Administration - Victor Enrique Sarmiento-Ortega; Diana Moroni-González; Alfonso Diaz; Miguel Ángel García-González; Eduardo Brambila; Samuel Treviño (Metabolites, 2023)
Metabolic diseases are a worldwide health problem. Insulin resistance (IR) is their distinctive hallmark. For their study, animal models that provide reliable information are necessary, permitting the analysis of the cluster of abnormalities that conform to it, its progression, and time-dependent molecular modifications. We aimed to develop an IR model by exogenous insulin administration. The effective dose of insulin glargine to generate hyperinsulinemia but without hypoglycemia was established. Then, two groups (control and insulin) of male Wistar rats of 100 g weight were formed. The selected dose (4 U/kg) was administered for 15, 30, 45, and 60 days. Zoometry, a glucose tolerance test, insulin response, IR, and the serum lipid profile were assessed. We evaluated insulin signaling, glycogenesis and lipogenesis, redox balance, and inflammation in the liver. Results showed an impairment of glucose tolerance, dyslipidemia, hyperinsulinemia, and peripheral and time-dependent selective IR. At the hepatic level, insulin signaling was impaired, resulting in reduced hepatic glycogen levels and triglyceride accumulation, an increase in the ROS level with MAPK-ERK1/2 response, and mild pro-oxidative microenvironmental sustained by MT, GSH, and GR activity. Hepatic IR coincides with additions in MAPK-p38, NF-κB, and zoometric changes. In conclusion, daily insulin glargine administration generated a progressive IR model. At the hepatic level, the IR was combined with oxidative conditions but without inflammation.